2008
DOI: 10.1007/s12098-008-0160-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an educational program on parental knowledge of cerebral palsy

Abstract: Parental knowledge of cerebral palsy is inadequate. A single-session educational program can significantly improve parental knowledge about many 'core basic issues' regarding cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
2
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 15 publications
6
31
2
16
Order By: Relevance
“…This is line with the study of Karande et al conducted on parents of children newly diagnosed with CP, about 80.8% of the respondents are not aware of the cause of the condition before educational intervention [1], another study conducted by Arora, et al 2014 on parents of children with CP also indicated low or lack knowledge of CP before the educational intervention in about 74.6% of the participants [9]. After the educational intervention all respondents (100%) attributed the cause of CP to pregnancy abnormalities, this is similar to the study of Karande et al that showed improvement of the knowledge of participants on the cause of cerebral palsy, about 76.9% of the participants could correctly explain the cause of cerebral palsy [1]. A study by Arora, et al confirmed our finding that 90.6% of the participants were able to mention the possible causes of CP [9].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This is line with the study of Karande et al conducted on parents of children newly diagnosed with CP, about 80.8% of the respondents are not aware of the cause of the condition before educational intervention [1], another study conducted by Arora, et al 2014 on parents of children with CP also indicated low or lack knowledge of CP before the educational intervention in about 74.6% of the participants [9]. After the educational intervention all respondents (100%) attributed the cause of CP to pregnancy abnormalities, this is similar to the study of Karande et al that showed improvement of the knowledge of participants on the cause of cerebral palsy, about 76.9% of the participants could correctly explain the cause of cerebral palsy [1]. A study by Arora, et al confirmed our finding that 90.6% of the participants were able to mention the possible causes of CP [9].…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted by Karande et al contradicts the finding of the study that majority of the respondents 69.2% were able to mention few professionals involved in the management of CP [1] although the studies differ in respondents as the study involves parents of children with CP and the respondents in our study are pregnant women with no CP children. But post awareness result showed a lot of improvements to about 88.5% of the respondent were able to identify more medical practitioners in the management of CP which is similar to our finding in the study that about 94.6% and 81.1% of responses are physiotherapist and paeditricans respectively involved in management of CP.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations